ATTENUATION OF SEISMIC WAVES IN RANDOM MEDIA - Fayzullin I.S.; Shapiro S.A. (My University, 1988)
The model of a medium with randomly distributed inhomogeneities is used to analyze the scattering properties of rocks on the basis of data on the fluctuations of the seismic wave field in them. But the capabilities of the model could be greatly expanded if fuller use were made of the attenuation parameter and if the scattering and absorbing properties of the rocks were determined separately. The introduction of this improvement is prevented by misconceptions as to the nature of the attenuation of seismic waves. Thus, it is assumed that the effective attenuation coefficient is represented by the sum of the scattering coefficient and the absorption coefficient. In the present paper we demonstrate that these and other phenomena can be explained under the model of a randomly inhomogeneous medium and that to a first approximation, the scattering and absorbing properties of the medium can be evaluated separately.